Penerapan Algoritma Minimax pada Permainan Tradisional Catur Jawa Skala 3x3 untuk Meningkatkan Daya Tarik Pemain - Muhammad Farras Muttaqin (Paradigma, 2018)
The Java Chess game is a traditional Java Chess game, which uses a 3x3 scale board game size and is played by 2 (two) players. Each player has a number of pawns as many as 3 (three) pieces are arranged horizontally. The win-ning condition can be achieved, if one player succeeds in preparing the first third vertically, diagonally or horizon-tally in the opposite position. Around the 1980s The game was known by the people of Indonesia. However, in the Year 2018, the Indonesian people's attraction on this Game is declining. Because today the Indonesian people pay less attention to the traditional game, instead they are more focused on the game more modern. Therefore, to restore their anthusiasm to the game of Java Chess, one way is to digitize the game. To make it happen, researchers use the Minimax Algorithm as Artificial Intelligence on Java Chess game. Researchers use Web Programming Language, which is HTML (Hypertext Markup Language), CSS (Cascading Style Sheets) and PHP (Hypertext Preprocessor) in designing Minimax implementation simulation Application on Java-Based Chess game.